1999
DOI: 10.1073/pnas.96.24.13857
|View full text |Cite
|
Sign up to set email alerts
|

The delayed resurgence of equatorial forests after the Permian–Triassic ecologic crisis

Abstract: In conjunction with the Permian-Triassic ecologic crisis Ϸ250 million years ago, massive dieback of coniferous vegetation resulted in a degradation of terrestrial ecosystems in Europe. A 4-to 5-million-year period of lycopsid dominance followed, and renewed proliferation of conifers did not occur before the transition between Early and Middle Triassic. We document this delayed re-establishment of equatorial forests on the basis of palynological data. The reconstructed pattern of vegetational change suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
2
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(134 citation statements)
references
References 39 publications
9
120
2
3
Order By: Relevance
“…This conclusion is in contrast to the opinion of Hallam (1991), who, on the basis of reefbuilding organisms, estimated that the biotic recovery after the end-Permian extinction might have taken some 5 myr following a prolonged survival stage through the earliest Triassic. Our conclusion also contrasts sharply with those of Erwin and Pan (1996), Foote (1996) and Looy et al (1999) based on gastropod and crinoid faunas and terrestrial coniferous vegetation respectively, and is also in disagreement with Erwin (1998), who suggested that the Early Triassic biotic recovery took place some 3±9 million years after the end-Permian extinction. It is thus clear that signi®cant discrepancies exist among the estimations about the timing of recovery in the Triassic, and that these discrepancies may well re¯ect the fact that the timing of recovery was different for different marine taxonomic groups and in different ecosystems or biogeographical regions.…”
Section: M P L I C a T I O N S F O R T H E T I M I N G O F B I O T contrasting
confidence: 56%
“…This conclusion is in contrast to the opinion of Hallam (1991), who, on the basis of reefbuilding organisms, estimated that the biotic recovery after the end-Permian extinction might have taken some 5 myr following a prolonged survival stage through the earliest Triassic. Our conclusion also contrasts sharply with those of Erwin and Pan (1996), Foote (1996) and Looy et al (1999) based on gastropod and crinoid faunas and terrestrial coniferous vegetation respectively, and is also in disagreement with Erwin (1998), who suggested that the Early Triassic biotic recovery took place some 3±9 million years after the end-Permian extinction. It is thus clear that signi®cant discrepancies exist among the estimations about the timing of recovery in the Triassic, and that these discrepancies may well re¯ect the fact that the timing of recovery was different for different marine taxonomic groups and in different ecosystems or biogeographical regions.…”
Section: M P L I C a T I O N S F O R T H E T I M I N G O F B I O T contrasting
confidence: 56%
“…If the results of (12) are valid, they suggest the recovery involves positive feedback, and the active creation of ecospace (12,13), similar to that recently proposed on the basis of a recent analysis of the delayed recovery of forests in the Early Triassic after the end-Permian mass extinction (15). This pattern of positive feedback is a likely feature of biotic recoveries, irrespective of the validity of ref.…”
Section: Recoveries and Biodiversity Dynamicsmentioning
confidence: 68%
“…The weedy lycopsid Isoetes diversified rapidly and dominated many Early Triassic assemblages (49). Looy et al (15) documented a long period of dominantly opportunistic lycopsid pollen into the Spathian stage, when a rapid diversification occurs in Europe. The recovery of this equitorial conifer assemblage corresponds to the recovery of higher latitude peat forests, ending the ''coal gap'' (50, 51).…”
Section: Postextinction Recoveries: Case Studiesmentioning
confidence: 99%
“…Along with the various other climate effects that have been hypothesized for the End-Cretaceous bolide impact (O'Keefe & Ahrens 1989;Gupta et al 2001), the destruction of forest canopies in its immediate aftermath may be expected to have resulted in substantially less precipitation until the vegetation recovered, as well as a temperature increase owing to the loss of transpirational cooling-an effect that is seasonally as large as 58C in the Amazon basin today (figures 1, 3 and 4). Alternatively, the degradation of non-angiosperm vegetation during earlier events, such as the End-Permian (Looy et al 1999) or Triassic/ Jurassic extinctions (McElwain et al 2009), would have had a much smaller feedback with climate. Thus, angiosperm evolution should be a consideration in future studies of mass extinctions and other environmental perturbations like the Palaeocene/Eocene Thermal Maximum (Wing et al 2005) because the same angiosperm-initiated climate modifications that contribute to the high diversity of angiosperm ecosystems may also make those ecosystems prone to more exaggerated responses to environmentally destructive events.…”
Section: Discussionmentioning
confidence: 99%